2014
DOI: 10.1186/s12888-014-0224-9
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal cohort study of depression, post-traumatic stress, and alcohol use in South African women who attend alcohol serving venues

Abstract: BackgroundIn South Africa, alcohol use poses a public health burden. Hazardous alcohol use often co-occurs with psychological distress (e.g., depression and post-traumatic stress). However, the majority of the research establishing the relationship between alcohol use and psychological distress has been cross-sectional, so the nature of co-occurring changes in psychological distress and alcohol use over time is not well characterized. The objective of this study is to examine the longitudinal relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
2
6
1
Order By: Relevance
“…Comorbid depression and PTSD during pregnancy can be especially harmful for perinatal health, as one recent study found that a combined diagnosis of depression and PTSD quadrupled the risk of preterm delivery (Yonkers et al, 2014). Future work must explore this co-occurrence and how to treat both conditions simultaneously in South Africa (Abler et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Comorbid depression and PTSD during pregnancy can be especially harmful for perinatal health, as one recent study found that a combined diagnosis of depression and PTSD quadrupled the risk of preterm delivery (Yonkers et al, 2014). Future work must explore this co-occurrence and how to treat both conditions simultaneously in South Africa (Abler et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…PTSS did contribute to both symptoms of alcohol dependence and depression, which is not surprising given the associations between these three disorders [60] as well as the bidirectional interaction between PTSD and alcohol [61]. The significant association between symptoms of alcohol dependence and depression may be due to the physiological effects that alcohol can have on increasing depressive symptoms [62].…”
Section: Discussionmentioning
confidence: 99%
“…13 Studies looking at both population and clinical samples in the province have also confirmed the association between psychiatric comorbidity and substance use disorders. 16,17,18,19…”
Section: Introductionmentioning
confidence: 99%
“…18 Abler et al investigated alcohol use, post-traumatic stress disorder and depressive symptoms in South African women who attended alcohol-serving venues and described the complex interplay between these three problems. 19…”
Section: Introductionmentioning
confidence: 99%